Reducing homelessness: An intergovernmental challenge. - Callahan, Richard F.; Redburn, Steve; Larson, Lauren; Riley, Brad (Public Administration Review)
To increase understanding of the intergovernmental dimension of addressing homelessness, the National Academy of Public Administration in 2022 formed a Working Group of Academy Fellows. In researching three case studies that have had a measure of success, local leaders reached across geographic and functional boundaries to forge agreement on shared goals and joint strategy. Five basic tasks at the local level contributed to effective initiatives: One, defining, committing to, and communicating the challenge of homelessness, with agreement on shared objectives and a coordinated strategy. Two, building a network to coordinate the contributions of each partner. Three, designing and delivering timely integrated services by aligning federal and state programs to the local context. Four, collecting, using, and sharing data to inform planning and targeted delivery of assistance. Five, building or strengthening governance and financing structures that support continued action and learning to sustain and improve local efforts over time.